PENGARUH SELF EFFICACY, KECERDASAN EMOSIONAL, TEKANAN KETAATAN, KOMPLEKSITAS TUGAS DAN TINGKAT SENIORITAS TERHADAP AUDIT JUDGMENT AUDITOR (Studi Pada KAP Wilayah Pekanbaru, Medan dan Padang) - Rizki Yuni Pratiwi; Restu Agusti; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research is to analyze the effect of self efficacy, emotional quotient, obedience pressure, task complexity and the level of seniority on the auditor’s audit judgment. Self Efficacy refers to the belief that a person has capacity to organize and execute the course of action required to produce the desired outcome. Emotional Quotient refers to the ability to recognize and control own feeling in any confusing situation, while Obedience Pressure comes from department/company there were audited or high rank officer and from professional standards. Task Complexity is defined as the numerous tasks that come continiously, difficult then confusing the auditor and The Level of Seniority is defined the duration of auditor actively do audit. This research used population of auditor who works in Public Accounting Office (KAP) in Pekanbaru, Medan and Padang. Sampling method in this research is the purposive sampling and the total number of respondent who made a sample on this research is 57 respondent. The analyzed method used in this research is outer model and inner model by using the application SmartPLS (Partial Least Square) ver.3. The result of this research showed that self efficacy, emotional quotient, obedience pressure, task complexity and the level of seniority affect the auditor’s audit judgment.Keywords: audit judgment, self efficacy, obedience pressure, task complexity, the level of seniority